A racionalidade tecnológica na universidade: uma análise crítica da legislação da pós-graduação brasileira na sociedade industrial do capitalismo tardio - Sá, Cristiane Regina Fairbanks de (2023)
The objective of this thesis is to identify how the Brazilian University is subject to the technological rationality in the industrial society of late capitalism, especially in postgraduate studies, through a critical analysis of the trends presented in the legislation that regulates it, but also the mechanisms of resistance existing in the legislation itself, thus seeking to explain which is the postgraduation social function at the current time. The deepening of the reasons of the reasons in the socio-historical context about the constitution of the University in the world, and about its constitution in Brazil is opportune because it allows understanding the origin of the different existing models, as well as their influence on the Brazilian model, elucidating its current constitution. In order to carry out this research, a database was constituted with the current Federal Legislation and documents that regulate the Brazilian Post-Graduation, and, through the determination of five categories of analysis, the observation of the relation of this content with the reality of the Post-Graduation based on the theoretical reference, intending to identify the trends presented in the legislation that regulates the university and post-graduation, as well as identifying the existence of resistance to this tendency. The categories to be analyzed are: (1) Didactic-scientific, administrative, and financial and asset management autonomy, (2) Evaluation of Brazilian postgraduate courses, (3) Financing of Brazilian postgraduate courses, (4) Background and knowledge of Brazilian researchers and (5) Research, Innovation and Technology and Impact & Social Insertion. This study is carried out from the perspective of the Critical Theory of Society, considering the theoretical contributions of Herbert Marcuse, Theodor Adorno, Max Horkheimer and Walter Benjamin, and Brazilian authors who study the Brazilian university, such as Darcy Ribeiro, Florestan Fernandes, Luiz Antonio Cunha. The use of this referential aims to understand the complexity of the social function of the Brazilian university today and to identify the contradictions presented in it. The analysis is carried out based on the concepts of Bildung (Humboldtian university), technological rationality (Marcuse), academic background (Adorno), and on the notions of closure of the universe of locution (Marcuse). As opposed to the background of the individual's entire personality, contemporary undergraduate and postgraduate educational background has the characteristic – in the vast majority – of being a quick, uncritical background, focused on the qualification of the individuals to supply the labor market, allowing the reproduction of late capitalism in industrial society completely dominated by the ideology of technological rationality